2007
DOI: 10.1093/ndt/gfn082
|View full text |Cite
|
Sign up to set email alerts
|

A health economic analysis of screening and optimal treatment of nephropathy in patients with type 2 diabetes and hypertension in the USA

Abstract: In patients with type 2 diabetes and hypertension, screening for nephropathy and treatment with a renoprotective-based antihypertensive agent was projected to improve patient outcomes and represent excellent value in a US setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 35 publications
0
58
0
2
Order By: Relevance
“…Two sensitive input parameters in one-way sensitivity analysis showed positive predictive value and the cost of tests. Results different from those of Palmer et al in that sensitivity analysis showed benefits of cost and outcomes of the screening in type 2 diabetes with hypertension; especially in patients at the age of 40 years [31][32]. On the other hand, Kiberd et al [35] reported that annual costs of ESRD were moderately sensitive to the model, whereas screening and drug cost had little effect.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Two sensitive input parameters in one-way sensitivity analysis showed positive predictive value and the cost of tests. Results different from those of Palmer et al in that sensitivity analysis showed benefits of cost and outcomes of the screening in type 2 diabetes with hypertension; especially in patients at the age of 40 years [31][32]. On the other hand, Kiberd et al [35] reported that annual costs of ESRD were moderately sensitive to the model, whereas screening and drug cost had little effect.…”
Section: Discussionmentioning
confidence: 76%
“…The costeffectiveness was found only in high-risk groups with hypertension and proteinuria [30]. Palmer et al reported that screening for microalbuminuria and overt nephropathy in diabetic patients with hypertension and use of renoprotective agents was cost-effective in the USA and France [31][32]. Proteinuria screening in subjects without diabetes or hypertension for early treatment with ACEI to delay progression of nephropathy was not cost-effective, except in highrisk groups such as the elderly, hypertensives, and diabetic patients [33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Health economic analyses have shown that screening for albuminuria in the Type 2 diabetic patients and subsequent initiation of angiotensin II antagonists treatment in those found positive contributed to better outcomes, including reduction of cardiovascular event, and may represent an excellent value. 31,32 On the other hand, some have argued that simply treating all middle-aged diabetic patients with angiotensinconverting enzyme inhibitors is a simple strategy that provides additional benefit at modest additional cost. 33 For the general population, a strategy of annual dipstick screening for gross proteinuria with follow-up testing and treatment with an angiotensin-converting enzyme inhibitor may not be cost-effective with regard to slowing progression of kidney disease or decreasing mortality.…”
Section: Lee Et Al Microalbuminuria and Stroke: Meta-analysis 2627mentioning
confidence: 99%
“…As DN progresses, there is an increase in urinary albumin excretion, observed as microalbuminuria and progressing to macroalbuminuria (4,5). Furthermore, after onset of DN, about 20% of individuals will progress to endstage renal diseases (ESRD) (6,7).…”
Section: Introductionmentioning
confidence: 99%